2017
DOI: 10.1111/jfpe.12638
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electric fields as an alternative to thermal processing for preservation of nutritive and physicochemical properties of beverages: A review

Abstract: Fruit juices and other beverages constitute an important source of bioactive compounds, but thermal processing may reduce their contents thus decreasing natural nutritive value of foods. This has been recently led to the use of non‐thermal technologies, especially pulsed electric fields (PEF) as an interesting alternative to thermal pasteurization of beverages. Reported results show that PEF is a useful for pasteurization of fruit juices that can minimize changes in physicochemical and nutritional properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 124 publications
(185 reference statements)
1
58
0
5
Order By: Relevance
“…Regarding the impact of such technology on plant-based beverages, Cortés et al [42] investigated the effect of PEF processing on the quality attributes of "horchata" (tiger nut milk), a typical plant-based beverage from Spain [47]. The study evaluated the impact of treatment time (100-475 microseconds) and electric field intensity (20-35 kV/cm) during 5 days at 5 • C, while the temperatures during the treatment did not exceed 35 • C. According to the authors, the pH decrease during storage was ameliorated by PEF treatment that was even more influenced by treatment time.…”
Section: Novel Methods Plant-based Milks Treatment Conditions Inferencmentioning
confidence: 99%
“…Regarding the impact of such technology on plant-based beverages, Cortés et al [42] investigated the effect of PEF processing on the quality attributes of "horchata" (tiger nut milk), a typical plant-based beverage from Spain [47]. The study evaluated the impact of treatment time (100-475 microseconds) and electric field intensity (20-35 kV/cm) during 5 days at 5 • C, while the temperatures during the treatment did not exceed 35 • C. According to the authors, the pH decrease during storage was ameliorated by PEF treatment that was even more influenced by treatment time.…”
Section: Novel Methods Plant-based Milks Treatment Conditions Inferencmentioning
confidence: 99%
“…Qian et al (2014) have examined the contribution of different PEF parameters to lipase inactivation in WBR samples, finding that the inhibitory effect was positively related to the frequency (200-1000 Hz), pulse width (3-15 μs), residence time (1-9 s), and voltage (3-15 V), while it was negatively influenced by the material thickness (5-25 mm). Moreover, voltage was found to be the main factor influencing microbial inactivation followed by pulse width and frequency (Gabrić et al, 2018).…”
Section: Pulsed Electric Fields (Pef)mentioning
confidence: 99%
“…Recently, the application of PEF in inactivating microorganisms has been extensively investigated and demonstrated Niu et al, 2019). Through applying highintensity electric pulses (1-80 kV cm À1 ) in several microseconds, the membrane constituents of cell would be changed and modified, including phospholipid bilayers and proteins (Gabri c et al, 2017). According to the theory of dielectric breakdown, the cell membrane permeability tends to be evidently enhanced, similar to that of electroporation when the field strength reaches 15-35 kV cm À1 and specific energies achieves 50-700 kJ kg À1 (Pu ertolas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of dielectric breakdown, the cell membrane permeability tends to be evidently enhanced, similar to that of electroporation when the field strength reaches 15-35 kV cm À1 and specific energies achieves 50-700 kJ kg À1 (Pu ertolas et al, 2010). With the development of processing and utilisation in bioactive products, PEF pretreatment within 0.7-3.0 kV cm À1 and 1.0-20 kJ kg À1 has attracted wide attention in the food mass transfer field (Gabri c et al, 2017). It has been reported that extraction of intracellular substances, such as juice yield, sugar, phenolics and astaxanthin (Loginova et al, 2012;Moussa-Ayoub et al, 2016;Yang et al, 2016;Zhi-Wei et al, 2018), tends to be strengthened by PEF, thus providing a good method to improve the food quality without significantly changing the temperature.…”
Section: Introductionmentioning
confidence: 99%